Analisis Normatif Perlindungan Hukum Hak Asasi Manusia Dalam Pemenuhan Hak Atas Informasi Dan Kebebasan Berpendapat - Cahyo Susilo (Journal of Contemporary Law Studies, 2026)
This study aims to analyze the regulation of human rights protection within the Indonesian legal system and to examine the role of the right to information and freedom of expression in strengthening democratic governance and the protection of constitutional rights in the digital era. The research employs a normative juridical method using statutory and conceptual approaches. Primary legal materials consist of the 1945 Constitution of the Republic of Indonesia, human rights legislation, and relevant international human rights instruments that have been adopted into the Indonesian legal framework. The study finds that Indonesia has established a comprehensive framework for human rights protection through constitutional guarantees, statutory regulations, judicial mechanisms, and the incorporation of international human rights principles. The right to information and freedom of expression function not only as fundamental rights, but also as instruments for public participation, government accountability, and social control within a democratic state governed by the rule of law. Nevertheless, the implementation of these rights continues to face challenges arising from the rapid development of digital technology, inconsistent legal interpretation, and the potential for excessive restrictions on civil liberties. Therefore, strengthening human rights–oriented legal interpretation and proportional regulatory mechanisms is necessary to ensure balanced protection between state authority and individual freedoms.